Stabilization of bis(chlorogermyliumylidene)s within bifunctional PNNP ligand frameworks and their reactivity studies. Issue 21 (21st March 2019) - Sahoo, Padmini; Raut, Ravindra K.; Maurya, Devesh; Kumar, Vikas; Rani, Pooja; Gonnade, Rajesh G.; Majumdar, Moumita
Abstract : Bis(chlorogermyliumylidene)s stabilized within the PNNP frameworks show diverse reactivity with Lewis bases, depending on the coordinated ligand backbone. Abstract : The diiminodiphosphine (Lim ) and diaminodiphosphines (l -NH andl -NMe) with a bifunctional PNNP ligand framework have been employed to host two [GeCl] + units leading to the formation of bis(chlorogermyliumylidene)1–3, respectively. The synthetic route involves a 1 : 2 stoichiometric reaction between the PNNP ligand and GeCl2 ·dioxane and the subsequent addition of two equivalents of chloride abstracting agent. Compound1 is unstable towards coordinating solvents and Lewis bases, resulting in the displacement of the GeCl unit and the formation of rearranged products4 and5 . However, the diaminodiphosphine coordinated Ge(ii ) bis(monocation)s2 and3 proved to be stable and revealed their electrophilic behaviour towards the Lewis bases studied.